Հայոց ցեղասպանությունը և հայ հոգևորականությունը 1915-1916 թթ. - Միքայել Մինասյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Геноцид нанес значительный ущерб армянской церкви и духовенству в Турции. Число армянских церквей и монастырей в 1912г. составляло более 2200. За время 1915-1918 гг. произошло варварское уничтожение, ограбление и разрушение около 2150 армянских церквей и монастырей со стороны турок. Погибло более 4000 священослужителей. The genocide has caused significant damage to the Armenian Church and to clergy in Turkey. A number of the Armenian churches and monasteries in 1912 formed more than 2200. During 1915-1918 there was a barbarous destruction, robbery and destruction of about 2150 Armenian churches and monasteries by the Turks. More than 4000 clerics were killed.
Keywords: Քրիստոնեություն; Հայոց եկեղեցի